Existence of solutions for solitons type equations in several space dimensions: Derrick’s Problem with (r,p)-Laplacian - Taibi, N. E.; Dellal, A.; Henderson, J.; Ouahab, A. (Methods of Functional Analysis and Topology, 2022)
In this paper we study a class of Lorentz invariant nonlinear field equations in several space dimensions. The main purpose is to obtain soliton-like solutions with twice (r,p)-Laplacian. The fields are characterized by a topological invariant, which we call the charge. We prove the existence of a static solution which minimizes the energy among the configurations with nontrivial charge. У статті вивчається клас нелінійних рівнянь, інваріантних відносно лоренцевих перетворень, для поля з декількома просторовими зміними. Основною метою є отримання солітоноподібних розв’язків з подвійним (r,p)-лапласіаном. Поля характеризуються топологічним інваріантом, який ми називаємо зарядом. Доведено існування статичного розв’язку, який мінімізує енергію в конфігураціях з нетривіальним зарядом.